Pengorganisasian Taman Pendidikan Al-Quran (Tpa) Dalam Upaya Meningkatkan Mutu Manajemen Pendidikan Islam Di Desa Pandansari Kecamatan Sine Kabupaten Ngawi - Muasomah, Luluk; Muthi'ah, Binti Nuriyatul; Irmawati, Devi; Listiani, Ana; Rubbiyati, Anis; Syaifudin, Arif; Alamsyah, Bahrul; Nisa, Faizi; Nashiroh, Iffatun; Faturrohman, Jerly Rifki; Ubaidillah , M. Alfin; Firdaus, Maulana Ahmad Fajar; Sani, Muhammad; Waluyo, Nazhila Tika; Fitrianti, Ratna; Mahmudah, Roif Uswatun; Lestari, Siska Rahayu (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
This Community Service Practice focuses on improving the quality of management of the Al-Quran Education Park (TPA) in Pandansari Village, Sine District, Ngawi Regency, East Java. Even though there are several TPAs ??in Pandansari, there are TPAs ??that are less effective in managing and complying with the curriculum of the Al-Qur'an Kindergarten Development and Development Institute-Indonesian Mosque Youth and Youth Communication Agency (LPPTKA-BKPRMI) thus having an impact on the quality of education management Al-Qur'an. This research aims to improve landfill management through a comprehensive training program. This training equips educators with the tools and knowledge to align with the curriculum. So that it can increase the effectiveness of teaching at the Al-Quran Education Park. After the training, a Follow-up Plan (RTL) was carried out including distributing guidebooks and administration. Assistance in implementing the Curriculum of the Al-Qur'an Kindergarten Development and Development Institute-Indonesian Mosque Youth Communication Agency (LPPTKA-BKPRMI) has gone well. The socialization and distribution of all Guidebooks and Administration has been well distributed. All Al-Quran Education Parks in Pandansari Village accept and are willing to implement it in their respective Al-Quran Education Parks (TPA). However, some TPAs ??only accept some. Like TPA Baitul Hasyim, it is ready to implement a Cash Administration Book. And the Kholid Hasyim TPA has almost been completely implemented, only the Cash Administration Book has not been accepted. This research shows the importance of systematic management in improving Islamic education and suggests that further support and monitoring is needed for continuous quality improvement. Keywords: Organizing, Al-Qur'an Education Park (TPA), Pandansari village